2016
DOI: 10.1016/j.apcatb.2015.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous Ti-incorporated SBA-15 with enhanced activity and durability for high-quality biodiesel production: Synthesis and utilization of the P123 template as carbon source

Abstract: A one-pot and environmental-friendly route to synthesizing carbonaceous Ti-SBA-15 materials as weakly Lewis solid acids for transesterification of Jatropha oil with methanol to high-quality Jatropha biodiesel fuel (BDF) was successfully developed. The chemical environment and location of Ti species were controlled by the molar ratios of hydrochloride (HCl) to titanium tetraisoproproxide (TTIP) in the Ti precursors. With a HCl/TTIP molar ratio of 2.5, the tetrahedrally coordinated Ti species with weakly Lewis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…High-resolution transmission electron microscopy (HRTEM) images were also obtained. In the in situ DRIFT spectra with pyridine adsorption (Figure 3A), the characteristic DRIFT signals centered at 1442 and 1540 cm −1 are assigned to pyridine adsorbed on Lewis and Bronsted acid sites, respectively [18][19][20]. The DRIFT signal centered at 1442 cm −1 is stronger than others, indicating that mesoporous sulfide catalysts are mostly related to Lewis solid acids.…”
Section: Characterizations Of the Mesoporous Sulfide Catalystsmentioning
confidence: 97%
“…High-resolution transmission electron microscopy (HRTEM) images were also obtained. In the in situ DRIFT spectra with pyridine adsorption (Figure 3A), the characteristic DRIFT signals centered at 1442 and 1540 cm −1 are assigned to pyridine adsorbed on Lewis and Bronsted acid sites, respectively [18][19][20]. The DRIFT signal centered at 1442 cm −1 is stronger than others, indicating that mesoporous sulfide catalysts are mostly related to Lewis solid acids.…”
Section: Characterizations Of the Mesoporous Sulfide Catalystsmentioning
confidence: 97%
“…In another study conducted by Chen et al, (2016b), a carbonaceous Ti-SBA-15 catalyst for transesterification of jatropha oil with methanol was successfully developed. The result showed that the catalyst gave excellent activity and durability in the synthesis of high-quality jatropha biodiesel, which fulfills the specification of international fuel standard.…”
Section: Titanium As Catalyst Support In the Transesterification Reacmentioning
confidence: 99%
“…Over the past few years, we have cooperated with Thai researchers to investigate the production of nonedible jatropha‐oil‐derived BDF on a pilot plant scale (1 ton d −1 ). Given that Jatropha curcas , as a nonedible plant, can be grown on dry land, it is generally agreed that jatropha‐oil‐derived BDF (hereinafter referred to as BDF for conciseness) has a low environmental and food supply impact . In view of the aforementioned technical problems, the above BDF (exhibiting poor oxidation stability) must be upgraded before use in high blends.…”
Section: Composition and Fuel Properties Of Bdfs A–cmentioning
confidence: 99%